Gambaran Pengetahuan Ibu Hamil Tentang Tanda Bahaya Kehamilan di Wilayah Kerja Puskesmas Mapilli Desa Segerang - Sitti Aras Diana; Irmayanti Irmayanti (Institut Nalanda, 2026)
Pregnancy danger signs are conditions that may threaten the health of both the mother and the fetus if they are not recognized and managed promptly. Pregnant women's knowledge of pregnancy danger signs is essential for supporting early detection and preventing complications during pregnancy. This study aimed to describe the level of knowledge of pregnant women regarding pregnancy danger signs in the working area of Mapilli Community Health Center (Puskesmas Mapilli), Segerang Village. This quantitative study employed a descriptive research design. The study population consisted of pregnant women residing in the working area of Puskesmas Mapilli, Segerang Village. Data were collected using a questionnaire containing questions about pregnancy danger signs. The data obtained were analyzed using univariate analysis and presented in the form of frequency distributions and percentages. The results showed that the majority of respondents had a good level of knowledge regarding pregnancy danger signs, with 11 respondents (78.6%) categorized as having good knowledge. Meanwhile, 3 respondents (21.4%) had a sufficient level of knowledge, and none of the respondents (0%) had poor knowledge. These findings indicate that most pregnant women had a good understanding of pregnancy danger signs. In conclusion, the level of knowledge of pregnant women regarding pregnancy danger signs in the working area of Puskesmas Mapilli, Segerang Village, was predominantly in the good category. Therefore, health education and counseling efforts should be maintained and enhanced to sustain and further improve pregnant women's knowledge in recognizing pregnancy danger signs at an early stage.